Xây dựng mô hình canh tác trên đất dốc do hộ nông dân quản lý - Lê, Khắc Huy (Bộ Giáo dục và Đào tạo, 2013)
Building up SALT model by planting forest trees on the top hill, making irrigntion systems and planting geen manure trees as hedgerows along the contour lines on the middle to reduce soil erosion, improve soil fertilizer and preserve water in order to Improve crops rotation. SALT products be able to get high and suitable productivity for minority people in Aluoi district , Thua Thien Hue province. Anyway, a lots of bare hills are used to grown many kind of crops so it contributes food security for people who lives in highland moutainous areas.